Evaluasi Kinerja Sistem Hidroponik Terintegrasi Dengan Teknologi Monitoring Lingkungan - * Prasetyo (Jurnal Ilmu Agroteknologi Indonesia, 2025)
Plant growth and quality in hydroponic systems are highly influenced by environmental conditions. This study aimed to evaluate the performance of a hydroponic system integrated with environmental monitoring technology using sensors and the Internet of Things (IoT). Lettuce (Lactuca sativa) was cultivated in two groups: a manual system and an integrated system, for 60 days. Measured parameters included plant growth (height, number of leaves, biomass), harvest quality (water content, nutrient levels), and environmental conditions (pH, temperature, electrical conductivity, humidity, light intensity). Results indicated that the integrated system improved plant growth by 20–25% compared to the manual system, maintained stable environmental parameters, and enhanced harvest quality. Statistical analysis revealed a significant positive correlation between environmental stability and plant performance. This study confirms that integrating monitoring technology into hydroponic systems provides significant benefits for productivity, quality, and operational efficiency in modern agriculture.